BLOODY DIARRHOEA IN A CHILD, COULD IT BE SCHISTOSOMIASIS? - Alvi, Muhammad Arshad; Alghamdi, Sharifa; Seerat, Iqtadar; al Matarfi, Omar (Journal of Ayub Medical College Abbottabad, 2017)
Schistosomiasis may cause diverse symptoms and it is usually not considered as a cause of disease especially in patients with normal immune system. We are reporting an eleven-year-old child who was initially diagnosed as a case of lymphoma but later on proved to be a case of acute schistosomiasis. Keywords: Bloody diarrhoea; Hyper-eosinophilia; Colonoscopy; Schistosomiasis